The rhetoric of the page - Maguire, Laurie E. 1959- (Oxford University Press, 2020)
This wide-ranging and entertaining book explores blank space from incunabula to Google books. Blanks are a paradox-simultaneously nothing and something, gesturing to what was once there or might be there. They are also a creative opportunity for readers as well as writers: readers respond to what is not there and writers come to anticipate that response. Thus, blank space develops literary and ludic applications. 0Each chapter focuses on one typographical form of what is not there on the page: physical gaps (Chapter One), marks of incompletion such as &c (Chapter Two), and the asterisk as a stand-in for things that cannot be said (Chapter Three). By looking at the early-modern page as a visual unit as well as a verbal unit, this volume shows how the relationship between textual layout and textual content is as productive for writers as it is for readers. Mise-en-page influences readers in the same way that rhetoric influences readers. It is thus possible to speak of 'the rhetoric of the page'
Keywords: Geschichte 1500-1700; Buchproduktion; Layout; Typografie; England; English literature / Early modern, 1500-1700 / History and criticism; Printing / History / Early modern, 1500-1700; Graphic design (Typography) / History / Early modern, 1500-1700; Layout (Printing) / History / Early modern, 1500-1700; English literature / Early modern; 1500-1700; Criticism, interpretation, etc; History